RESPON PERTUMBUHAN DAN HASIL TANAMAN WIJEN (Sesamum indicum L) KULTIVAR WINAS I AKIBAT PERLAKUAN PUPUK KALIUM (KCl) DAN KOMPOS - Fitriani, Ira; Faqih , Achmad; Purnomo, Dwi (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2022)
This experiment aims to know . Growth Response and Yield of Sesame Plants (Sesamum indicum L.) Cultivars of Winas I Due to Treatment of Potassium Fertilizer (KCl) and Compost. The experiment was carried out in Mekarjaya Gantar Indramayu Village – West Java. The time of the study in August - November 2021. The experimental method was an experiment with a Randomized Group Design (RAK), with two treatments repeated three times. Namely the combined treatment of potash fertilizer application (50 kg / ha, 100 kg / ha and 150 kg / ha). With a dose of compost (5 tons/ha, 7.5 tons/ha, 10 tons/ha). Data processing used linear models of statistical tests, fingerprint analysis, and further test analysis of the scott-knot cluster and to determine the correlation between the treatment and the growth component and the sesame yield, namely with the Product Moment correlation coefficient. Experimental results: (1) Potash fertilizer and compost treatment affects plant height, Number of leaves per clump of umyrrh 14 HST, 28 HST, Leaf Area Index 14 HST, 28 HST, trunk diameter, number of branches, root volume, plant growth rate, number of pitted pods per clump, number of pitted pods per plot, weight of pods per clump, weight of pods per plot, dry seed weight per clump, dry seed weight per plot, but no effect on the number of leaves at the age of 42 HST, Leaf Area Index aged 42 HST, number of hollow pods per cluster and weight of 1000 seeds. (2) Combination of Potassium treatment of 150 kg: 10 tons of compost reaches the largest weight of dry seeds per plot, which is 1.4 kg / plot or equivalent to 2.32 tons / ha. (3) There is a marked correlation between plant height aged 14 HST, 28 HST and 42 HST with strong, medium and strong correlation categories, as well as the number of leaves aged 14 HST, 28 HST and 42 HST with dry seed weights per plot with strong, strong, and medium correlation categories.